Pengembangan Aplikasi Perencanaan Karier (Si Peka) - Deka Ramanta; Adi Atmoko; Diniy Hidayatur Rahman (Jurnal Pendidikan Humaniora, 2022)
Abstract: The purpose of this research and development is to produce a product in the form of a career planning application media to facilitate career planning for students at SMA Negeri 1 Lawang which is theoretically and practically acceptable in terms of feasibility, appropriateness, attractiveness, convenience and usability. Based on the validation results from experts and prospective users, the results show that the career planning application has received theoretical and practical acceptance in terms of feasibility, appropriateness, attractiveness, convenience and usability. Based on the results of the field implementation test, it was found that the career planning application was very effectively used by students to facilitate and support career planning for high school students.Abstrak: Tujuan dari penelitian dan pengembanagn ini adalah menghasilkan produk berupa media aplikasi perencanaan karier (Si Peka) untuk menfasilitasi perencanaan karier peserta didik di SMA Negeri 1 Lawang yang berterima secara teoritis dan praktis dari segi kelayakan, kepatutan, kemenarikan, kemudahan dan kebergunaan. Berdasarkan hasil validasi dari ahli dan calon pengguna, diperoleh hasil bahwa aplikasi perencanaan karier (Si Peka) mendapatkan keberterimaan secara teoritis dan praktis dari segi kelayakan, kepatutan, kemenarikan, kemudahan dan kebergunaan. Berdasarkan hasil uji pelaksanaan lapangan diperoleh bahwa aplikasi perencaan karier (Si Peka) sangat efektif digunakan peserta didik untuk memfasilitasi dan menunjang perencanaan karier peserta didik SMA.